High-modulus rotary jet spun co-polyimide nanofibers and their composites - James J. Rogalski (Taylor & Francis Group, 2020)
The production of high-modulus and high-strength polymer nanofibers using centrifugal or rotary jet spinning (RJS) was explored. Co-polyimide nanofibers based on 3,3′,4,4′-biphenyl-tetracarboxylic dianhydride (BPDA)/p-phenylenediamine (PDA)/4,4′-oxydianiline (ODA) (BPO) were successfully spun by RJS from a polyamic acid precursor solution before conversion into highly oriented and chain extended BPO co-polyimide fibers via an imidization step. Fourier transform infrared (FTIR) characterization was used to evaluate the chemical conversion of the fibers. Nanocomposite laminates based on co-polyimide nonwoven fiber mats in epoxy were manufactured for mechanical testing. Analysis using the generalized rule of mixtures resulted in a back-calculated fiber modulus and strength of around 50 and 2 GPa, approaching that of high-performance fibers like Kevlar® 29, and equaling those of co-polyimide fibers obtained via electrospinning, making them the strongest centrifugal spun fibers ever reported.